Metabolic Engineering of Saccharomyces cerevisiae for Heterologous Carnosic Acid Production - Wei, Panpan; Zhang, Chuanbo; Bian, Xueke; Lu, Wenyu (Frontiers in Bioengineering and Biotechnology, 2022)
Carnosic acid (CA), a phenolic tricyclic diterpene, has many biological effects, including anti-inflammatory, anticancer, antiobesity, and antidiabetic activities. In this study, an efficient biosynthetic pathway was constructed to produce CA in Saccharomyces cerevisiae. First, the CA precursor miltiradiene was synthesized, after which the CA production strain was constructed by integrating the genes encoding cytochrome P450 enzymes (P450s) and cytochrome P450 reductase (CPR) SmCPR. The CA titer was further increased by the coexpression of CYP76AH1 and SmCPR~t28SpCytb5 fusion proteins and the overexpression of different catalases to detoxify the hydrogen peroxide (H2O2). Finally, engineering of the endoplasmic reticulum and cofactor supply increased the CA titer to 24.65 mg/L in shake flasks and 75.18 mg/L in 5 L fed-batch fermentation. This study demonstrates that the ability of engineered yeast cells to synthesize CA can be improved through metabolic engineering and synthetic biology strategies, providing a theoretical basis for microbial synthesis of other diterpenoids.